Preparation method and application of high-sulfur pyrobase sodium ion battery negative electrode material

By impregnating high sulfur coke with copper chloride solution and two-stage heat treatment processes, a high-performance sodium ion battery negative electrode material was prepared, which solved the problem of insufficient performance of sodium ion battery negative electrode material in the prior art, and achieved the effect of high discharge capacity and high cycle retention.

CN119833533AActive Publication Date: 2025-04-15EAST CHINA UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510180856.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-15
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

The existing sodium ion battery anode materials have shortcomings in the first week of Coulomb efficiency and cycle stability, making it difficult to achieve high-performance sodium ion batteries.

Method used

High sulfur coke is used as the basic material, and high-performance sodium ion battery negative electrode material is prepared through impregnation with copper chloride solution and two-stage heat treatment processes. Specific steps include pulverizing the mixing of high-sulfur coke and copper chloride solution, two-stage heat treatment and pickling.

Benefits of technology

The high discharge capacity and high cycle retention rate of sodium ion batteries have been achieved. The first Coulomb efficiency and capacity retention rate after 1,000 cycles have been significantly improved, and the desulfurization rate can reach 95.3%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833533A_ABST
    Figure CN119833533A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a high-sulfur pyrobase sodium ion battery negative electrode material, and relates to the technical field of new energy electronic materials. The method comprises the following steps: (1) mixing crushed high-sulfur coke with a copper chloride solution according to a certain proportion, and dipping; carrying out suction filtration after dipping, washing until the filtrate is neutral, and drying; (2) carrying out two-stage heat treatment on the high-sulfur coke obtained in the step (1) in an argon gas environment, (3) cooling the roasted high-sulfur coke obtained in the step (2), carrying out acid pickling by using hydrochloric acid, carrying out suction filtration after acid pickling, washing until filtrate is neutral, and drying; and (4) carrying out ball milling on the material treated in the step (3) to obtain the high-sulfur pyrobase sodium ion battery negative electrode material. According to the invention, the electrochemical performance of the sodium ion battery assembled by the high-sulfur pyrobase sodium ion battery negative electrode material is improved by using copper chloride infiltration and secondary heating processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy electronic materials, and in particular to a preparation method and application of a negative electrode material for a sodium ion battery. Background Art

[0002] Sodium-ion batteries are rechargeable batteries that use sodium ions as charge carriers. The main advantages of sodium-ion batteries over traditional lithium-ion batteries are that sodium resources are abundant, low-cost, and widely distributed. Sodium-ion batteries work in a similar way to lithium-ion batteries, storing and releasing energy through the movement of sodium ions between the positive and negative electrodes. Due to the large volume of sodium ions, the energy density of sodium-ion batteries is generally lower than that of lithium-ion batteries, but in the field of large-scale energy storage, sodium-ion batteries show great potential due to their cost advantages and safety. With technological advances, the performance of sodium-ion batteries is gradually improving, and they are expected to play an important role in the future energy storage market.

[0003] The current status of research on negative electrode materials for sodium-ion batteries shows that carbon-based materials have become the main research direction due to their abundant resources, low cost, high reversible capacity and good cycle stability. Hard carbon materials increase the active sites for sodium ion storage due to their developed nanopores and gaps between primary particles, and the pore adsorption effect can improve the rate performance of carbon materials. Soft carbon materials have higher carbon content and commercial potential, but the tendency to graphitize during high-temperature carbonization will affect sodium ion storage. In addition to carbon materials, researchers are also exploring non-carbon materials such as titanium-based compounds, alloy materials, metal compounds and organic compounds. Although these materials have high theoretical specific capacity, their cycle performance is poor due to problems such as low conductivity, large volume change and easy pulverization. The current research focuses on improving the first-cycle coulombic efficiency, improving voltage hysteresis and cycle stability.

[0004] High sulfur petroleum coke, referred to as high sulfur coke in the present invention, is a byproduct produced in the process of petroleum refining, and its sulfur content is usually above 3%wt. This coke has the appearance of a dark brown porous solid irregular block, similar to a sponge, so it is sometimes also called sponge coke. Due to its high sulfur characteristics, high sulfur coke is mainly used in chemical production, or as a fuel for industries such as metal casting and glass factories. In the electrochemical industry, low-cost high sulfur coke has not yet achieved high value-added applications.

[0005] As an example, Chinese patent CN115818617B discloses a method for preparing negative electrode active materials for sodium ion batteries from high-sulfur coke. The high-sulfur coke and transition metal salt are pre-ammoniation roasted in an ammonia atmosphere, then calcined under negative pressure, and then washed and dried to obtain a high-sulfur-based negative electrode active material; the sulfur content in the high-sulfur coke is 3.5 ~ 8wt.%; the weight ratio of the high-sulfur coke and the transition metal salt is 100:2 ~ 20; the temperature of the ammoniation roasting stage is 500 ~ 700℃; the calcination temperature is 800 ~ 1200℃; the transition metal salt is at least one of iron salt, cobalt salt, nickel salt, and manganese salt; the volume content of ammonia in the ammonia atmosphere is 5 ~ 20%; the ammoniation roasting stage is carried out at normal pressure; the ammoniation roasting time is 2 ~ 6h; the negative pressure is 20 ~ 500Pa; the calcination time is 2 ~ 4h. The battery assembled with the electrode material prepared by this method has a maximum specific capacity of 276 mAh / g, and a capacity retention rate of 93.3% after 500 cycles.

[0006] Therefore, it is urgent to develop a new method for preparing high-sulfur coke-based sodium ion battery negative electrode materials to achieve higher first coulombic efficiency and high cycle retention rate of sodium ion batteries. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing and applying a negative electrode material for a sodium ion battery based on a high-sulfur coke. The present invention provides a method for preparing a negative electrode material for a sodium ion battery, wherein a high-sulfur coke is treated with a specific process to prepare a high-performance negative electrode material for a sodium ion battery. A sodium ion battery using the negative electrode material as an electrode has an initial coulombic efficiency and a high cycle retention rate, and expands the application of high-sulfur coke in the field of electrochemistry.

[0008] To achieve the above objectives, the present invention provides the following technical solutions: A method for preparing a negative electrode material for a high-sulfur coke-based sodium ion battery, characterized by comprising the steps of: (1) Mixing the crushed high-sulfur coke with a copper chloride solution in a certain proportion and impregnating the mixture; after impregnation, filtering and washing the mixture until the filtrate is neutral, and drying the mixture; (2) subjecting the high-sulfur coke obtained in step (1) to two-stage heat treatment in an argon gas environment, wherein the first stage of the heat treatment is to rapidly heat the temperature to 900-1100° C. and keep the temperature for a period of time; and the second stage of the heat treatment is to heat the temperature again to 2200-3000° C. based on the temperature reached in the first stage of the heat treatment and keep the temperature for a period of time; (3) cooling the calcined high-sulfur coke obtained in step (2), washing it with hydrochloric acid, filtering it with suction, washing it until the filtrate is neutral, and drying it; (4) The material obtained by the treatment in step (3) is ball-milled to a particle size of 5 to 10 μm, thereby obtaining a high-sulfur coke-based sodium ion battery negative electrode material.

[0009] Furthermore, the mass fraction of copper chloride in the copper chloride solution is 10% to 30%.

[0010] Furthermore, the particle size of the high-sulfur coke after crushing in step (1) is 0.05-0.1 mm.

[0011] Furthermore, in step (1), the mass ratio of high-sulfur coke to cupric chloride solution is 1:2 to 1:6.

[0012] Furthermore, in step (1), the high-sulfur coke is immersed in the copper chloride solution for 10 to 15 hours.

[0013] Furthermore, the heating rate of the first stage of rapid heating in the step (2) is 10-50°C / min.

[0014] Furthermore, in the step (2), after the first stage of heat treatment is heated to the target temperature, the heat preservation time is 1 to 2.5 hours.

[0015] Furthermore, in the step (2), after the second stage heat treatment is heated to the target temperature, the heat preservation time is 2 to 4 hours.

[0016] The present invention also provides a high-sulfur coke-based sodium ion battery negative electrode material, which is prepared using the above method.

[0017] The present invention also provides an application of a high-sulfur coke-based sodium ion battery negative electrode material, wherein the material is used as a negative electrode active material for preparing a sodium ion battery.

[0018] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art, as an example: The high-sulfur coke-based sodium ion battery negative electrode material prepared by the preparation method provided by the present invention, and the sodium ion battery assembled with the material have high discharge capacity and cycle retention rate, and the capacity retention rate is 94.1% after 1000 cycles.

[0019] The preparation method provided by the present invention roasts high-sulfur coke by rapidly heating up the temperature, so that the high-sulfur coke is cracked to generate pores, and the organic phase sulfur in the high-sulfur coke which is difficult to meet the requirements of sodium ion batteries is removed; wherein, the addition of copper chloride further promotes the removal of sulfur at high temperature, and the final desulfurization rate can reach 95.3%; The preparation method provided by the present invention shrinks the pores through high-temperature treatment, thereby increasing the closed porosity. The prepared material has a low specific surface area and is suitable for use as a negative electrode material for sodium ion batteries.

[0020] The material prepared by the preparation method provided by the present invention has high discharge capacity and high capacity retention rate, and expands the application of high-sulfur coke in the field of electrochemistry. The above characteristics and advantages make it have good application prospects as a negative electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a charge and discharge curve diagram of a sodium ion battery made from the high-sulfur coke-based sodium ion battery negative electrode material prepared in Example 5 provided by the present invention. DETAILED DESCRIPTION

[0022] The preparation method and application of the high-sulfur coke-based sodium ion battery negative electrode material disclosed in the present invention are further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0023] Techniques, methods, and devices known to those of ordinary skill in the relevant art may not be discussed in detail, but where appropriate, the techniques, methods, and devices should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0024] Technical term explanation: Specific capacity (mAh / g): refers to the amount of electrical energy that can be stored and released per unit mass of battery material, usually expressed in milliampere-hours per gram. Specific capacity is one of the important indicators for evaluating battery performance, which reflects the energy density and energy storage capacity of the battery under specific conditions.

[0025] First coulombic efficiency: refers to the ratio between the amount of electricity actually released during the discharge process and the amount of electricity input during the charging process in the first charge and discharge cycle of the battery. It is usually expressed as a percentage. The first coulombic efficiency is one of the important indicators for evaluating battery performance and cycle stability, especially in rechargeable batteries such as lithium-ion batteries and sodium-ion batteries.

[0026] Capacity retention rate after 1000 cycles: refers to the ratio between the remaining capacity of the battery and its initial capacity after 1000 charge and discharge cycles. This indicator reflects the performance stability and durability of the battery after long-term use, usually expressed as a percentage. Embodiment 1

[0027] It should be noted that the sulfur content of the high-sulfur coke used in the embodiments of the present invention is 4-8wt%.

[0028] The raw material high-sulfur coke is placed in a crusher for crushing and sieved by a screening machine. Take 10g of high-sulfur coke particles with a median particle size of 0.05mm for use. Weigh 6g of copper chloride and dissolve it in 24g of deionized water, stir evenly to completely dissolve the copper chloride, and obtain a 20wt% copper chloride solution. Immerse 10g of high-sulfur coke particles in the copper chloride solution, stir to mix it evenly, and continue stirring for 12h. After the impregnation is completed, use a Buchner funnel to filter. After filtration, rinse the high-sulfur coke particles with deionized water to wash off the copper chloride solution on the surface of the particles until the filtrate is neutral, and put the filtered high-sulfur coke particles into an oven for drying.

[0029] The dried high-sulfur coke particles are placed in a high-temperature tubular furnace, argon is introduced, and the temperature is raised to 1000°C at a heating rate of 30°C / min, and kept warm for 2 hours; then the temperature is raised to 2500°C at a heating rate of 2°C / min, and kept warm for 3 hours. After the heat treatment is completed, the high-sulfur coke particles are cooled and placed in a Buchner funnel. First rinse with hydrochloric acid, then rinse with deionized water until the filtrate is neutral, filter and put into an oven to dry. After drying, the obtained material is ball-milled using a ball milling equipment, and ball-milled at a speed of 300r / min for 2 hours to obtain a high-sulfur coke-based sodium ion battery negative electrode material.

[0030] The high-sulfur coke-based sodium ion battery negative electrode material prepared in this embodiment was assembled into a sodium ion battery in a glove box filled with argon and the electrochemical performance was tested. The specific capacity of the hard carbon negative electrode material reached 291.2 mAh / g, the first coulombic efficiency was 85.7%, and the capacity retention rate after 1000 cycles was 94.1%. Embodiment 2

[0031] The raw material high-sulfur coke is placed in a crusher and crushed, and sieved by a screening machine. 10g of high-sulfur coke particles with a median particle size of 0.05mm are taken for standby. 5g of copper chloride is weighed, dissolved in 45g of deionized water, and stirred evenly to completely dissolve the copper chloride to obtain a 10wt% copper chloride solution. 10g of high-sulfur coke particles are placed in the copper chloride solution for immersion, stirred to mix evenly, and stirred continuously for 10h. After the impregnation is completed, use a Buchner funnel to filter, and after filtering, rinse the high-sulfur coke particles with deionized water to wash away the copper chloride solution on the surface of the particles until the filtrate is neutral, and the high-sulfur coke particles after filtering are placed in an oven for drying.

[0032] The dried high-sulfur coke particles were placed in a high-temperature tubular furnace, argon was introduced, and the temperature was raised to 1000°C at a heating rate of 30°C / min, and kept warm for 2 hours; then the temperature was raised to 2800°C at a heating rate of 2°C / min, and kept warm for 4 hours. After the heat treatment, the high-sulfur coke particles were cooled, placed in a Buchner funnel, first rinsed with hydrochloric acid, and then rinsed with deionized water until the filtrate was neutral. After filtration, it was placed in an oven for drying. After drying, the obtained material was ball-milled using a ball milling equipment, and ball-milled at a speed of 300r / min for 2 hours to obtain a high-sulfur coke-based sodium ion battery negative electrode material.

[0033] The high-sulfur coke-based sodium ion battery negative electrode material prepared in this embodiment was assembled into a sodium ion battery in a glove box filled with argon and the electrochemical performance was tested. The specific capacity of the hard carbon negative electrode material reached 287.7 mAh / g, the first coulombic efficiency was 80.3%, and the capacity retention rate after 1000 cycles was 94.2%. Embodiment 3

[0034] The raw material high-sulfur coke is crushed in a crusher, sieved by a screening machine, and 10g of high-sulfur coke particles with a median particle size of 0.1mm are taken for use. Weigh 10g of copper chloride and dissolve it in 40g of deionized water, stir evenly to completely dissolve the copper chloride, and obtain a 20wt% copper chloride solution; 10g of high-sulfur coke particles are immersed in the copper chloride solution, stirred to mix evenly, and stirred continuously for 14h. After the impregnation is completed, use a Buchner funnel to filter, and then rinse the high-sulfur coke particles with deionized water to wash away the copper chloride solution on the surface of the particles until the filtrate is neutral. Put the filtered high-sulfur coke particles into an oven for drying.

[0035] The dried high-sulfur coke particles were placed in a high-temperature tubular furnace, argon was introduced, and the temperature was raised to 900°C at a heating rate of 10°C / min, and kept warm for 1.5 hours; then the temperature was raised to 3000°C at a heating rate of 2°C / min, and kept warm for 3 hours. After the heat treatment, the high-sulfur coke particles were cooled, placed in a Buchner funnel, first rinsed with hydrochloric acid, and then rinsed with deionized water until the filtrate was neutral. After filtration, it was placed in an oven for drying. After drying, the obtained material was ball-milled using a ball milling equipment, and ball-milled at a speed of 300r / min for 2 hours to obtain a high-sulfur coke-based sodium ion battery negative electrode material.

[0036] The high-sulfur coke-based sodium ion battery negative electrode material prepared in this embodiment was assembled into a sodium ion battery in a glove box filled with argon and the electrochemical performance was tested. The specific capacity of the hard carbon negative electrode material reached 284.3 mAh / g, the first coulombic efficiency was 82.3%, and the capacity retention rate after 1000 cycles was 93.4%. Embodiment 4

[0037] The raw material high-sulfur coke is placed in a crusher for crushing, sieved by a screening machine, and 10g of high-sulfur coke particles with a median particle size of 0.05mm are taken for standby use. Weigh 10g of copper chloride and dissolve it in 40g of deionized water, stir evenly to completely dissolve the copper chloride, and obtain a 20wt% copper chloride solution. 10g of high-sulfur coke particles are placed in the copper chloride solution for immersion, stirred to mix evenly, and stirred continuously for 12h. After the impregnation is completed, use a Buchner funnel for suction filtration, and after suction filtration, rinse the high-sulfur coke particles with deionized water to wash away the copper chloride solution on the surface of the particles until the filtrate is neutral. The high-sulfur coke particles after suction filtration are placed in an oven for drying.

[0038] The dried high-sulfur coke particles were placed in a high-temperature tubular furnace, argon was introduced, and the temperature was raised to 1100°C at a heating rate of 40°C / min, and kept warm for 2.5 hours; then the temperature was raised to 2200°C at a heating rate of 2°C / min, and kept warm for 2 hours. After the heat treatment, the high-sulfur coke particles were cooled, placed in a Buchner funnel, first rinsed with hydrochloric acid, then rinsed with deionized water until the filtrate was neutral, and then filtered and placed in an oven for drying. After drying, the obtained material was ball-milled using a ball milling equipment, and ball-milled at a speed of 300r / min for 2 hours to obtain a high-sulfur coke-based sodium ion battery negative electrode material.

[0039] The high-sulfur coke-based sodium ion battery negative electrode material prepared in this embodiment was assembled into a sodium ion battery in a glove box filled with argon and the electrochemical performance was tested. The specific capacity of the hard carbon negative electrode material reached 298.9 mAh / g, the first coulombic efficiency was 79.8%, and the capacity retention rate after 1000 cycles was 92.5%. Embodiment 5

[0040] The raw material high-sulfur coke is placed in a crusher for crushing, sieved by a screening machine, and 10g of high-sulfur coke particles with a median particle size of 0.05mm are taken for standby use. Weigh 10g of copper chloride, dissolve it in 40g of deionized water, stir evenly to completely dissolve the copper chloride, and obtain a 20wt% copper chloride solution. 10g of high-sulfur coke particles are placed in the copper chloride solution for immersion, stirred to mix evenly, and stirred continuously for 12h. After the impregnation is completed, use a Buchner funnel for suction filtration, and after suction filtration, rinse the high-sulfur coke particles with deionized water to wash away the copper chloride solution on the surface of the particles until the filtrate is neutral. The high-sulfur coke particles after suction filtration are placed in an oven for drying.

[0041] The dried high-sulfur coke particles were placed in a high-temperature tubular furnace, argon was introduced, and the temperature was raised to 1000°C at a heating rate of 30°C / min, and kept warm for 2 hours; then the temperature was raised to 2500°C at a heating rate of 2°C / min, and kept warm for 3 hours. After the heat treatment, the high-sulfur coke particles were cooled, placed in a Buchner funnel, first rinsed with hydrochloric acid, then rinsed with deionized water until the filtrate was neutral, and then filtered and placed in an oven for drying. After drying, the obtained material was ball-milled using a ball milling equipment, and ball-milled at a speed of 300r / min for 2 hours to obtain a high-sulfur coke-based sodium ion battery negative electrode material.

[0042] The high-sulfur coke-based sodium ion battery negative electrode material prepared in this embodiment was assembled into a sodium ion battery in a glove box filled with argon and the electrochemical performance was tested. The specific capacity of the hard carbon negative electrode material reached 297.8 mAh / g, the first coulombic efficiency was 82.6%, and the capacity retention rate after 1000 cycles was 94.1%.

[0043] Comparative Example The raw high-sulfur coke is crushed in a crusher, sieved by a sieving machine, and 10g of high-sulfur coke particles with a median particle size of 0.05mm are taken for use. 10g of high-sulfur coke particles are placed in a Buchner funnel, and the high-sulfur coke particles are rinsed with deionized water, and the filtered high-sulfur coke particles are placed in an oven for drying.

[0044] The dried high-sulfur coke particles were placed in a high-temperature tubular furnace, argon was introduced, and the temperature was raised to 1000°C at a heating rate of 5°C / min, and kept warm for 2 hours; then the temperature was raised to 2500°C at a heating rate of 2°C / min, and kept warm for 3 hours. After the heat treatment, the high-sulfur coke particles were cooled, placed in a Buchner funnel, and rinsed with deionized water until the filtrate was neutral. After filtration, they were placed in an oven for drying. After drying, the obtained material was ball-milled using a ball milling equipment, and ball-milled at a speed of 300r / min for 2 hours to obtain a high-sulfur coke-based sodium ion battery negative electrode material.

[0045] The high-sulfur coke-based sodium ion battery negative electrode material prepared in this comparative example was assembled into a sodium ion battery and the electrochemical performance test was performed. The specific capacity of the hard carbon negative electrode material reached 261.5 mAh / g, the initial coulombic efficiency was 70.1%, and the capacity retention rate after 1000 cycles was 83.8%. See Table 1 for a performance comparison of the sodium ion batteries obtained in Example 5 and the comparative example.

[0046]

[0047] As can be seen from the above table, in the present invention, due to the use of copper chloride infiltration and two-stage heat treatment processes, the sodium ion battery assembled from the high-sulfur coke-based sodium ion battery negative electrode material prepared in Example 5 has a higher specific capacity, first coulomb efficiency and better capacity retention rate, indicating that the battery has better charge and discharge performance and energy storage performance.

[0048] See also Figure 1 As shown, it is a charge and discharge curve diagram of a sodium ion battery made of a high-sulfur coke-based sodium ion battery negative electrode material prepared in Example 5 provided by the present invention. It can be seen from the figure that the discharge curve of the sodium ion battery has a steep portion at the beginning, which indicates that the battery can be charged externally relatively quickly. During the discharge process, the charge and discharge platform is relatively wide, indicating that the battery has voltage stability and can provide continuous current output. The discharge curve of the battery remains stable near the cut-off voltage, which can better protect the battery.

[0049] The high-sulfur coke-based sodium ion battery negative electrode material provided by the present invention can be used to prepare sodium ion batteries. In addition, the material can also be used in the fields of electric vehicles, energy storage systems, portable electronic devices, etc.

[0050] For other technical features, please refer to the description of the previous embodiment and will not be repeated here.

[0051] In the above description, the disclosure of the present invention is not intended to limit itself to these aspects. Rather, within the scope of the target protection of the present disclosure, the components can be selectively and operatively combined in any number. All technical, scientific or other terms are consistent with the meanings understood by those skilled in the art unless they are limited to the opposite meaning. Common terms found in dictionaries should not be interpreted too idealistically or too impractically in the context of relevant technical documents unless the present disclosure clearly defines them as such. Any changes and modifications made by a person of ordinary skill in the field of the present invention based on the above disclosure belong to the scope of protection of the claims.

Claims

1. A method for preparing a negative electrode material for a high-sulfur coke-based sodium ion battery, characterized in that Includes steps: (1) Mixing the crushed high-sulfur coke with a copper chloride solution in a certain proportion and impregnating the mixture; after impregnation, filtering and washing the mixture until the filtrate is neutral, and drying the mixture; (2) subjecting the high-sulfur coke obtained in step (1) to two-stage heat treatment in an argon gas environment, wherein the first stage of the heat treatment is to rapidly heat the temperature to 900-1100° C. and keep the temperature for a period of time; and the second stage of the heat treatment is to heat the temperature again to 2200-3000° C. based on the temperature reached in the first stage of the heat treatment and keep the temperature for a period of time; (3) cooling the calcined high-sulfur coke obtained in step (2), washing it with hydrochloric acid, filtering it with suction, washing it until the filtrate is neutral, and drying it; (4) The material obtained by the treatment in step (3) is ball-milled to a particle size of 5-10 μm, thereby obtaining a high-sulfur coke-based sodium ion battery negative electrode material.

2. The preparation method according to claim 1, characterized in that: The mass fraction of copper chloride in the copper chloride solution is 10% to 30%.

3. The preparation method according to claim 1, characterized in that: The particle size of the high-sulfur coke after crushing in the step (1) is 0.05-0.1 mm.

4. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of high-sulfur coke to cupric chloride solution is 1:2-1:

6.

5. The preparation method according to claim 1, characterized in that: In the step (1), the high-sulfur coke is immersed in the copper chloride solution for 10 to 15 hours.

6. The preparation method according to claim 1, characterized in that: The heating rate of the first stage of rapid heating in step (2) is 10-50°C / min.

7. The preparation method according to claim 1, characterized in that: After the first stage of heat treatment in step (2) is heated to the target temperature, the heat preservation time is 1 to 2.5 hours.

8. The preparation method according to claim 1, characterized in that: After the second stage heat treatment in step (2) is heated to the target temperature, the heat preservation time is 2 to 4 hours.

9. A high-sulfur coke-based sodium ion battery negative electrode material, characterized in that: The material is prepared according to the preparation method according to any one of claims 1-8.

10. An application of a high-sulfur coke-based sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The material is used as a negative electrode active material for preparing a sodium ion battery.

Citation Information

Patent Citations

  • A sodium ion battery negative electrode active material made from high-sulfur coke, and its preparation method and application

    CN115818617B

  • Method for preparing prebaked anode with high-sulfur coke

    CN103031573A

  • Sodium-ion battery negative electrode active material prepared from high-sulfur coke as well as preparation method and application of sodium-ion battery negative electrode active material

    CN115818617A

  • Preparation method of graphite negative electrode material

    CN117263176A

  • Silicon-based negative electrode active material, secondary battery, and electric device

    WO2024183065A1